A Paper-Based IL-6 Test Strip Coupled With a Spectrum-Based Optical Reader for Differentiating Influenza Severity in Children - Lin, Sheng-Wen; Shen, Ching-Fen; Liu, Ching-Chuan; Cheng, Chao-Min (Frontiers in Bioengineering and Biotechnology, 2021)
Influenza virus infection is a major worldwide public health problem. Influenza virus infections are associated with a high hospitalization rate in children between the ages of 5 and 14, and a small percentage of these patients could develop more complicated and more severe symptoms, e.g., elevated fever, violent dry cough, pneumonia, and acute respiratory distress syndrome, that require admission to an intensive care unit. We developed an interleukin-6 test strip that used colloidal gold-conjugated antibodies to detect human interleukin-6 protein. These complexes were captured in perpendicular T lines that were pre-coated with anti-human interleukin-6 antibodies, where they subsequently presented as colored bands. This paper-based test strip could be used in combination with a spectrum-based optical reader. Full-spectrum interleukin-6 protein reflex optical signals are acquired from the spectral optical module to analyze interleukin-6 level in serum with standard quantification. We have retrospectively evaluated 10 children (23 serum samples) with severe influenza virus infections, 26 children (26 serum samples) with mild influenza virus infections and 10 healthy children (10 serum samples). Our system, a combination of a paper-based test strip and a spectrum-based optical reader, can provide both qualitative and quantitative information. When used with the optical reader, detection limit can be improved from a qualitative, naked-eye level of 400 pg/mL to a quantitative, optical reader level of 76.85 pg/mL. After monitoring the interleukin-6 level in serum via our system, we found a high correlation between our system and the conventional sandwich ELISA method (Rho = 0.706, p < 0.001). The sensitivity and specificity for differentiating between severe and mild influenza by test strip coupled with optical reader were 78.3% and 50.0%, respectively. Additionally, the sensitivity and specificity were 85.7% and 95.5% when interleukin-6 was combined with serum C-reaction protein, and the ROC area-under-the-curve was high as well (AUC=0.911, p < 0.001). The potential advantages of our system, i.e., paper-based test strip coupled with a spectrum-based optical reader, are as follows: 1) simple user operation; 2) rapid turnaround times – within 20 minutes; 3) high detection performance; and, 4) low-cost fabrication.